2014
DOI: 10.1016/j.proeng.2014.11.833
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Carbon-Graphene/Epoxy Hybrid Nanocomposites

Abstract: Plain strain fracture toughness (K IC ) of graphene-epoxy (G-Ep) and carbon-graphene-epoxy (C-G-Ep) hybrid nanocomposites have been evaluated using single-edge-notch bending (SENB) specimens. The effects of graphene concentrations on K IC have been examined. G-Ep nanocomposites were prepared using a combination of mechanical mixing, magnetic stirring, sonication and high shear mixing. The hybrid nanocomposites (C-G-Ep) were processed using manual layup techniques and vacuum assistance during curing process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The addition of nanoparticles such as graphene, graphene oxide, carbon nanotubes, and nanosilica could improve toughness and mechanical properties, thermal stability, and anticorrosion properties of ER . Carolan et al .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nanoparticles such as graphene, graphene oxide, carbon nanotubes, and nanosilica could improve toughness and mechanical properties, thermal stability, and anticorrosion properties of ER . Carolan et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, epoxy resins are generally brittle which restrict their applications. Hawkins et al [35,36] studied the fracture toughness and strain energy behavior of carbon-graphene/epoxy hybrid nanocomposites. GO-epoxy based nanocomposites also possess the flexural behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on hybrid filler technology in polymers, based on GO and MWCNT [13][14][15][16]. The results of this study open up many directions for further research on GO.…”
Section: Introductionmentioning
confidence: 66%
“…The increase in tensile, flexural, and impact strength is higher as a result of the limitations in molecular chain motion caused by the increased crosslinking of polymers, this increase being moderate enough to prevent the material from hardening to lead to embrittlement. This also causes a reduction in deformation leading to failure [14]. From the results of Figure 2, it shows that the hybrid materials at different combination ratios give good fire resistance (limited oxygen index reaches from 27.6 to 31% of the minimum oxygen for the material to ignite).…”
Section: Discussionmentioning
confidence: 95%